A model quantifying global vegetation resistance and resilience to short‐term climate anomalies and their relationship with vegetation cover. Issue 5 (2nd February 2015) - De Keersmaecker, Wanda; Lhermitte, Stef; Tits, Laurent; Honnay, Olivier; Somers, Ben; Coppin, Pol
Abstract Aim In order to mitigate the ecological, economical and social consequences of future climate change, we must understand and quantify the response of vegetation to short‐term climate anomalies. There is currently no model that quantifies vegetation resistance and resilience at a global scale while simultaneously taking climate variability into account. The goals of this study were therefore to develop a standardized indicator of short‐term vegetation resilience and resistance to drought and temperature anomalies, and to improve our understanding of vegetation resistance and resilience in drought‐sensitive areas by linking metrics of vegetation stability to the percentage of tree cover, non‐tree vegetation and bare soil. Location Global. Methods The deviation of vegetation behaviour from expectations was quantified using anomalies in the normalized difference vegetation index (NDVI) and modelled as a function of (1) past NDVI anomalies, (2) an instantaneous drought indicator and (3) temperature anomalies. Metrics of resistance and resilience were then extracted from the model and related to the percentages of bare soil, non‐tree vegetation and tree cover. Results Comparisons of the globally derived resilience and resistance metrics showed low resilience and low resistance to drought in semi‐arid areas, low resistance to negative temperature anomalies in high‐latitude areas, and low resistance to positive temperature anomalies in the Sahel and Australia. In drought‐sensitive areas, resilience was highest for vegetation types with 3–20% bare soil and 5–15% tree cover. Main conclusions Our ARx model is the first to simultaneously derive vegetation resistance and resilience metrics at a global scale, explicitly taking into account the spatial variability of short‐term climate anomalies and data reliability. Its results highlight the impact of tree cover, non‐tree vegetation and bare soil on vegetation resilience.